Diversity of medicinal plants at Khao Lommuak in Prachuap Khiri Khan Province, Thailand - N. Aggimarangsee (2018)
Khao Lommuak is a small and steep isolated limestone hill located on the eastern coast of peninsula Thailand. The primary natural habitat of the hill is forest over limestone hill, with some scrub and cultivated gardens at the base. As 90% of the hill's perimeter adjoins the sea, there are also some sea cliff vegetation, bare rocks and sandy beach. An 18-month study on the ecology and behavior of dusky langur (Trachypithecus obscurus), a type of monkey, was carried out at the site. Five botanical plots, each measuring 750 m2, were established so as to describe the vegetation of the langurs' habitats, and to obtain an ecological understanding of the langurs' behavior. Using a minimum of 20 cm girth measured at 120 cm vertically from the tree's base, a total of 304 sample trees, including medicinal plants, were obtained from these plots. Simpson's index for diversity of plant at the site was 0.72. This paper describes some currently known medicinal plants observed at this site, both within and outside the vegetation plots, and the use of these plants by humans and the langurs. © ISHS 2005.